2014
DOI: 10.1111/ppl.12231
|View full text |Cite
|
Sign up to set email alerts
|

Reduced seed germination in Arabidopsis over‐expressing SWI/SNF2 ATPase genes

Abstract: In the life of flowering plants, seed germination is a critical step to ensure survival into the next generation. Generally the seed prior to germination has been in a dormant state with a low rate of metabolism. In the transition from a dormant seed to a germinating seed, various epigenetic mechanisms play a regulatory role. Here, we demonstrate that the over-expression of chromatin remodeling ATPase genes (AtCHR12 or AtCHR23) reduced the frequency of seed germination in Arabidopsis thaliana up to 30% relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…On the basis of overexpression studies, it was suggested that MINU1 promotes growth arrest upon drought or heat stress in adult Arabidopsis plants (Mlynarova et al ., ). Overexpression of either MINU1 or MINU2 also reduces the rate of seed germination; the defect is more pronounced in conditions of salt, heat and ABA stress (Leeggangers et al ., ). The authors observed elevated expression of seed maturation genes ( AtS2 , At2S3 ) in MINU overexpressing plants, several of these are upregulated in brm mutants and direct BRM targets (Tang et al ., ).…”
Section: A Closer Look: Swi/snf and Chd3 Subfamily Chromatin Remodelimentioning
confidence: 97%
See 2 more Smart Citations
“…On the basis of overexpression studies, it was suggested that MINU1 promotes growth arrest upon drought or heat stress in adult Arabidopsis plants (Mlynarova et al ., ). Overexpression of either MINU1 or MINU2 also reduces the rate of seed germination; the defect is more pronounced in conditions of salt, heat and ABA stress (Leeggangers et al ., ). The authors observed elevated expression of seed maturation genes ( AtS2 , At2S3 ) in MINU overexpressing plants, several of these are upregulated in brm mutants and direct BRM targets (Tang et al ., ).…”
Section: A Closer Look: Swi/snf and Chd3 Subfamily Chromatin Remodelimentioning
confidence: 97%
“…MINU2 overexpression also caused reduced growth (Folta et al ., ). Intriguingly, expression of endogenous MINU1 and MINU2 in the wild type decreases during germination (Leeggangers et al ., ).…”
Section: A Closer Look: Swi/snf and Chd3 Subfamily Chromatin Remodelimentioning
confidence: 97%
See 1 more Smart Citation
“…PKL is required for about 80% of the gene expression changes triggered by GAs [184]. On the other hand, the repression of the CHR12/23 genes (SWI2/SNF2 subgroup ATPases) is required for full germination since their overexpression represses germination by elevating the levels of maturation-related genes [185].…”
Section: Germination Control By the Epigenomementioning
confidence: 99%
“…Not all mature seeds of a plant can grow into fertile plants. During the germination and growing processes of a mature seed, the surrounding environment is highly significant [ 4 , 5 ]. During transfer of the seed to a proper environment for further germination and growth, fruits play a crucial role [ 5 ].…”
Section: Introductionmentioning
confidence: 99%